Austrolebias robustus - Alonso, Felipe (2022)
Austrolebias robustus has most recently been assessed for The IUCN Red List of Threatened Species in 2020. Austrolebias robustus is listed as Vulnerable under criteria B2ab(iii,iv); D2.